Critical review of thermoelectrics in modern power generation applications - Saqr, Khalid M.; Musa, Md. Nor (VinÄ?a Institute of Nuclear Sciences, 2009)
The thermoelectric complementary effects have been discovered in the nineteenth century. However, their role in engineering applications has been very limited until the first half of the twentieth century, the beginning of space exploration era. Radioisotope thermoelectric generators have been the actual motive for the research community to develop efficient, reliable and advanced thermoelectrics. The efficiency of thermoelectric materials has been doubled several times during the past three decades. Nevertheless, there are numerous challenges to be resolved in order to develop thermoelectric systems for our modern applications. This paper discusses the recent advances in thermoelectric power systems and sheds the light on the main problematic concerns which confront contemporary research efforts in that field.